The high performance swimming coach as a leader : developing contextual fit - Robbins, P. (Lancaster University, 2019)
This thesis addresses the question of how a High Performance Swimming Coach (HPSC) in the UK, acting as a leader, develops a contextual fit for their role of facilitating elite athlete performance. The main goal of the research was to explore the nature of elite swimming coaching in order to reveal the factors that give an HPSC, from an ontological standpoint, feelings of being at home in their chosen career. The main theoretical perspectives used in the analysis of research data were leadership, including the concepts of management, and sociology. The sociological perspectives on leadership encompass the concepts of social interactionism and Pierre Bourdieu's habitus, capital and field. It became evident, in the early stages of the research, that an eclectic mix of theories would enable a more comprehensive and rounded analysis of the research data. The primary research method selected was a qualitative, single case study, although elements of phenomenology, heuristic inquiry and ethnography were also employed in the gathering of the research data. The aim was to gain first-hand accounts from elite swimming coaches in the UK, from an existential viewpoint, of their journey towards becoming an effective HPSC. Primary data for the research was collected from three sources: a purposive sample of 32 HPSCs from a range of swimming organisations across the UK; informal interviews and observations at major swimming competitions in the UK; and responses from high profile UK and international HPSCs involved in coaching forums at British Swimming Coaches Association (BSCA) annual conferences. Findings from the analysis revealed that HPSCs execute their role within five distinct social fields, which are all sources of mediating influences and determinants of contextual fit. These five generic fields are: the core HPSC-athlete field; the competition arena; the swimming organisation; UK Sport and British society. It is, however, the first three fields that exert the most social pressure on the HPSC and are the main focus for the research. The findings also revealed that the determinants of contextual fit are contextualised identity and contextualised leadership. Contextualised identity is realised when the HPSC becomes the embodiment of their swimming organisation within the five contextual fields. Relationships formed and the social influence that the HPSC has within the milieu define their contextualised leadership. All the 32 HPSCs interviewed showed high levels of personal drive and competitiveness and were ruthless regarding the standards they set themselves and expected from their athletes. As a counterbalance, however, to a tough no-nonsense approach, they exhibited high levels of emotional intelligence, emotional labour, and care for their athletes. Other factors revealed included highly developed contextual awareness, an insatiable hunger for swimming-related technical knowledge and a high learning agility. In their operational role, they displayed an ability to see what other coaches were unable to see, through a highly developed 'Coaching-Eye'. They could also build effective coachathlete relationships and project manage a team of technical support agents to meet the needs of their athletes competing on the world stage. Recommendations for further research and HPSC continued professional development include the Coaching-Eye, relationships, contracting with a range of stakeholders, project management and suggestions for future choices of theoretical perspectives for investigations into leadership phenomena.